Production potential and competition indices in potato (Solanum tuberosum) + French bean (Phaseolus vulgaris) intercropping system in Shimla hills - Dua, V K; Lal, S S; Govindakrishnan, P M (The Indian Journal of Agricultural Sciences, 2005)
An experiment was conducted at Shimla during 2001 and 2002 to evaluate different row ratios and cropping geometry in potato (Solanum tuberosum L.) + French bean (Phaseolus vulgaris L.) intercropping system. The potato was a dominant species when it was sown in lesser proportion than French bean, whereas French bean dominated potato in intercropping when its proportion was equal or less than that of potato. All the intercropping treatments showed yield advantage (LER &gt1) over the sole cropping. On the basis of land-equivalent ratio (1.4975) and compensation ratio (CoRa = 4.95; CoRb = 1.90), the maximum advantage from the intercropping of potato +French bean was obtained when planted in 2:2 row ratio with 100% population density of each crop.